A review of current modalities to treat cellulite effectively. Issue 4 (23rd November 2020) - Ferzli, Georgina; Sadick, Neil
Abstract: Edematous fibrosclerotic panniculopathy, better known as cellulite, is a skin condition that affects 80%–98% of postpubertal women. Cellulite is believed to be a result of the effects of estrogen on the dermal and subcutaneous fat, including but not limited to fibroblast proliferation, lipogenesis, adipocyte hypertrophy, and collagen formation. These findings are most commonly located in the buttocks, thighs, and abdomen. Not surprisingly, many women seek out treatment to minimize the appearance of cellulite. With a growing understanding of cellulite, there has also been substantial growth in the treatment options available to target the problem. Topical agents, energy‐based devices, injectable treatments, and surgical treatments have all been used to treat cellulite, with significant studies performed to ensure the safety and efficacy of each. In this article, we will discuss these available treatments for cellulite.